The retina of the lab rat: focus on retinal ganglion cells and photoreceptors - Galindo-Romero, Caridad; Norte-Muñoz, María; Gallego-Ortega, Alejandro; Rodríguez-Ramírez, Kristy T.; Lucas-Ruiz, Fernando; González-Riquelme, María Josefa; Vidal-Sanz, Manuel; Agudo-Barriuso, Marta (Frontiers in Neuroanatomy, 2022)
Albino and pigmented rat strains are widely used in models to study retinal degeneration and to test new therapies. Here, we have summarized the main topographical and functional characteristics of the rat retina focussing on photoreceptors and retinal ganglion cells (RGCs), the beginning and end of the retinal circuitry, respectively. These neurons are very sensitive to injury and disease, and thus knowing their normal number, topography, and function is essential to accurately investigate on neuronal survival and protection.